The Role of Social Media Platforms in Enhancing Employee Creativity Through Knowledge Sharing Among Generation Z - Joan Jasmine, Veronika; Basrowi; Khaeruman (Center of Language and Cultural Studies, 2024)
characteristics and behaviors shaped by the digital era. As this generation is highly connected to technology and social media, companies face the challenge of harnessing their potential to drive creativity and innovation. This study examines the role of social media platforms in enhancing employee creativity through knowledge sharing among Gen Z employees in Serang City, Banten. Despite their digital fluency, innovation and creativity among Gen Z employess in the region have shown a decline over recent years. This research uses a quantitative approach, employing Structural Equation Modeling (SEM) to analyze data from 105 respondents. The results reveal that both work-related social media and social-related social media have a positive and significant impact on knowledge sharing, which in turn, enhances employee creativity.